SERVANT LEADERSHIP AND WORK SATISFACTION BETWEEN NURSING STAFF OF PUBLIC HOSPITALS IN PESHAWAR - Ali , Israr; Hashim, Muhammad; Bhatti, Anam; Ali, Zafer (International Journal of Psychosocial Rehabilitation, 2020)
Over recent years, servant leadership has been considered a popular paradigm for most service and manufacturing enterprises. This unique approach to attributes helped most modern companies thrive in this competitive environment. This model not only enables companies to fulfill their social responsibilities but also empowers employees, provides useful information, creates a sense of honesty, credibility, and much more spiritual training to retrieve workers from anxiety and depression. In public hospitals, three aspects of servant leadership (stewardship, emotional healing, and wisdom) were considered the essential predictors of employment satisfaction. This research was carried out in Peshawar public hospitals by taking nursing workers as a sample. Of the 4 major public hospitals in Peshawar, a total of 72 nursing staff was selected. A structured questionnaire was used to gather data. Data collection was done using a simple random technique. The results showed that the relationship between wisdom, emotional healing and stewardship, and satisfaction of nursing staff was positive. In the last section, more guidance and recommendations are given.